The influence of patient perception of physician empathy on patient satisfaction among attending physicians working with residents in an emergent care setting. Issue 3 (17th August 2021) - Kirby, Ryan; Knowles, Heidi C.; Patel, Anant; Alanis, Naomi; Rice, Colton; d'Etienne, James P.; Schrader, Chet D.; Zenarosa, Nestor R.; Wang, Hao
Abstract: Background: It is unclear whether the patient's perception of attending physician empathy and the patient's satisfaction can be affected when attending physicians work alongside residents. We aim to determine the influence residents may have on (1) patient perception of attending physician empathy and (2) patient satisfaction as it relates to their respective attending physicians. Methods: This is a prospective single‐center observational study. Patient perception of physician empathy was measured using Jefferson Scale of Patient Perception of Physician Empathy (JSPPPE) in both attendings and residents in the Emergency Department. Patient satisfaction with attending physicians and residents was measured by real‐time patient satisfaction survey. Multivariate logistic regressions were performed to determine the association between patient satisfaction and JSPPPE after patient demographics, attending physician different experience, and residents with different years of training were adjusted. Results: A total of 351 patients were enrolled. Mean JSPPPE scores were 30.1 among attending working alone, 30.1 in attending working with PGY‐1 EM residents, 29.6 in attending working with PGY‐2, and 27.8 in attending working with PGY‐3 ( p  < 0.05). Strong correlation occurred between attending JSPPPE score and patient satisfaction to attending physicians ( ρ  > 0.5). The adjusted odds ratio was 1.32 (95% CI 1.23‐1.41, p  < 0.001) on attending's JSPPPE score predicting patient satisfaction to the attending physicians. However, there were no significant differences on patient satisfaction among four different groups. Conclusion: Empathy has strong correlation with patient satisfaction. Decreased patient perception of attending physician empathy was found when working with senior residents in comparison to working alone or with junior residents.